Supramolecular Structure of Temperature‐Dependent Polymeric Hydrogels Modulated by Drug Incorporation. Issue 42 (16th November 2020) - Franco, Margareth K. K. D.; Sepulveda, Anderson F.; Vigato, Aryane A.; Oshiro, Alisson; Machado, Ian Pompermayer; Kent, Ben; Clemens, Daniel; Yokaichiya, Fabiano; de Araujo, Daniele Ribeiro
Abstract: Poloxamers or Pluronics® (PL) have been described as promising pharmaceutical and cosmetics matrices. Herein, we have explored the structural organization of hydrogel formulations composed of PL F‐127 and PL L‐81, considering their different hydrophilic‐lipophilic balances and interactions with an antimigraine drug, sumatriptan succinate (SMT). Hydrogels phase organizations were investigated by X‐ray diffraction (XRD) and Small Angle Neutron Scattering (SANS) to establish the relationship between structural features and drug release modulation. XRD analysis revealed very low intensity peaks for hydrogels containing SMT due to the presence of small amounts of SMT as crystalline form, which is an evidence of drug incorporation into hydrogels. At physiological temperature, a structural transition from lamellar to hexagonal was observed after SMT incorporation. In addition, SANS patterns displayed a distorted hexagonal structure, (calculated q 2 >experimental q 2 ), indicating the presence of a comprised structure compared to a perfect hexagonal assembly. This structural shift however have no influence on the drug release mechanism, allowing the SMT molecules to access the micellar and intermicellar hydrophilic spaces, with release mechanism dependent on the drug diffusion (R 2 =0.998 ≥ 0.986) from the hydrogel to the medium and release constant (Krel) values from 9.8 to 14.7 %.h −1 ; 31.5 to 39.1 %.h −1/2 ; 0.84 to 1.2 %.h −n for Zero‐order, Higuchi and Korsmeyer‐Peppas models, respectively. Using SMT as a drug model, it could be concluded that the drug access to the micellar/intermicellar hydrophilic spaces can be modulated by interplaying the polarity of binary PL‐based hydrogels. Therefore, drug release constants and mechanisms will be then dependent on the hydrogels physico‐chemical and structural properties, which determine the drug diffusion from the hydrogel to the release medium. Abstract : Thermosensitive copolymers are promising pharmaceutical and cosmetics matrices. Herein, we have explored the structural organization of poloxamer‐based (PL) hydrogels with hydrophilic‐lipophilic balances and interactions with an antimigraine drug, sumatriptan succinate (SMT). The hexagonal phase facilitates the drug incorporation into intermicellar spaces, being the preferential structure for evoking low drug release constant values. At physiological temperature and after drug incorporation, hydrogels display a distorted supramolecular structure when compared to drug‐free hydrogels, an important feature to predict their biopharmaceutical properties.